Association Between Activities of Daily Living and Sleep Quality Among Older Adults: A Cross-Sectional Study - Anggi Nur Maya Sari; Lukman Hakim; Miftahul Munir; Tiara Putri Ryandini (PT Pubsains Nur Cendekia, 2026)
Background: Aging is accompanied by progressive physiological decline that reduces older adults' functional capacity and independence in performing activities of daily living (ADL). Limitations in basic activities, such as walking, dressing, bathing, and transferring, may increase physical discomfort, dependence on others, and psychological distress, which can ultimately impair sleep quality. Aims: This study aimed to examine the relationship between activities of daily living and sleep quality among older adults in Lajo Lor Village, Singgahan District. Methods: A quantitative study with a non-experimental correlational design and cross-sectional approach was conducted among older adults in Lajo Lor Village. The study population consisted of 109 older adults, of whom 86 participants were selected using probability sampling with a simple random sampling technique. ADL independence was assessed using the Katz Index, while sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using Spearman's rank correlation test with a significance level of α = 0.05. Results: The analysis demonstrated a statistically significant relationship between activities of daily living and sleep quality (p < 0.001), with a very strong positive correlation (r = 0.871). Older adults who were more independent in performing daily activities tended to report better sleep quality. These findings indicate that maintaining functional independence may contribute to healthier sleep patterns, possibly through increased physical activity and reduced functional dependence. Conclusions: Activities of daily living are strongly associated with sleep quality among older adults. Greater independence in ADL is linked to better sleep quality, emphasizing the importance of interventions aimed at maintaining or improving functional independence to promote healthy sleep and enhance overall well-being in the aging population.